2015
DOI: 10.4314/star.v3i4.27
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Students’ Perceived EFL Classroom Climate and their Achievement in English Language

Abstract: Article Information This study attempts to investigate the relationship between students" perceived EFL classroom climate and their achievement in English language. The samples of the study were 200 grade 10 students at Gidole and Chencha Preparatory and Secondary schools in Ethiopia. In order to gather data for the study, classroom climate inventory questionnaire and English language achievement test were used. Pearson Product-Moment Correlation was used to examine correlations between students" perceived EFL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Teacher behavior includes teachers’ communication style, classroom management, expressing interest in student ideas, and offering help to students, while student behavior includes continuous involvement in activities, cooperation, and competition ( Garrett, 2008 ; Schiller, 2009 ; Brandmiller et al, 2020 ; Yang et al, 2020 ). Also, research suggests that a positive climate in the class can promote student learning motivation ( Peng, 2012 ; Joe et al, 2017 ), self-efficacy ( Lim and Fraser, 2018 ), achievement ( Gedamu and Siyawik, 2015 ), attitude ( Khajavy et al, 2016 ), and willingness to communicate ( Khajavy et al, 2018 ; Zhang et al, 2022 ). Motivated by the emerging field of positive psychology, FLE is defined as the perception of pleasure provided by the L2 learning classroom ( Lee, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Teacher behavior includes teachers’ communication style, classroom management, expressing interest in student ideas, and offering help to students, while student behavior includes continuous involvement in activities, cooperation, and competition ( Garrett, 2008 ; Schiller, 2009 ; Brandmiller et al, 2020 ; Yang et al, 2020 ). Also, research suggests that a positive climate in the class can promote student learning motivation ( Peng, 2012 ; Joe et al, 2017 ), self-efficacy ( Lim and Fraser, 2018 ), achievement ( Gedamu and Siyawik, 2015 ), attitude ( Khajavy et al, 2016 ), and willingness to communicate ( Khajavy et al, 2018 ; Zhang et al, 2022 ). Motivated by the emerging field of positive psychology, FLE is defined as the perception of pleasure provided by the L2 learning classroom ( Lee, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Classroom environment has been widely researched in different disciplines such as Math ( Aluri and Fraser, 2019 ), Science ( Fraser and Aldridge, 2010 ), and Biology ( Zeidan, 2010 ). It has also been studied in terms of EFL learning in different context which focuses on instruments development, learners and teachers’ perceptions of actual classroom environment ( Goksu, 2015 ), and how English classroom environment exerts its influence on learners’ achievement ( Gedamu and Siyawik, 2015 ), attitude ( Lim and Fraser, 2018 ), and engagement ( Hoi, 2022 ). For instance, Goksu (2015) examines how 166 Turkish high school students perceive their English classroom environment and the findings reveal that participants have positive perceptions and there are no grade and gender differences in their perceptions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(p.141). Nonetheless, a direct effect of the social climate of an EFL classroom, such as Task Challenge, Involvement, and Teacher Support, on students' English achievement has also been noticed (Gedamu & Siyawik, 2015). In addition, preceding research has indicated that male and female EFL students may have different perceptions of social climate elements (Bi, 2015;Lim & Fraser, 2018;Mohammadi & Aliakbari, 2018).…”
Section: Social Climate Of Classroommentioning
confidence: 99%